Application Of Financial Management Techniques And Its Impact On Performance Of Smes:Empirical Evidence From Jaffna Divisional Secretariat - Anandasayanan, S. (Faculty of Arts and Culture South Eastern University of Sri Lanka, 2025)
Financial management techniques are fundamental to the effective operation and long-term viability of business organizations. When these techniques are applied appropriately, they assist firms in utilizing resources efficiently and in achieving their objectives in a sustainable manner. This survey strived to explore how financial management techniques influence the performance of small and medium-sized enterprises (SMEs) in the Jaffna region. The study intensive on Working Capital Management, Investment Appraisal, Capital Structure, and Financial Reporting as exogenous variables, with SME performance considered as the endogenous variable. Using a random sampling approach, data were collected from 105 SMEs operating in the Jaffna Divisional Secretariat (DS) Division as of 31st December 2023 through structured questionnaires. The gathered data were examined using multiple regression techniques with the aid of the Statistical Package for Social Sciences (SPSS).The outcomes specify that Working Capital Management and Capital Structure practices exert a positive and statistically significant influence on SME performance. In light of these findings, the study emphasizes the weight of strengthening financial management techniques among SMEs, specifically in relation to optimizing capital structure and enhancing working capital efficiency. An appropriate mix of financing sources can reduce the likelihood of financial distress by maintaining sufficient liquidity to support day-to-day operations. Additionally, sound capital structure decisions enable SMEs to secure funds for growth related activities such as business expansion, mergers and acquisitions, research and development, and other strategic investments. Overall, the outcomes provide fruitful insights for SME owners and managers to withstand existing business and secure long-lasting sustainability via the proper adoption of financial management techniques.
Keywords: Capital structure; Financial reporting; Investment appraisal; SME’s performance; Working capital management